Clinical profile of alcohol dependent paintents according to Lesch Typology one year after the Covid-19 pandemic-comparative study - Dusan Kuljancic; Jelena Amidzic; Lazar Ljubotin; Djendji Siladji; Mina Cvjetkovic Bosnjak; Vladimir Knezevic; Dragana Ratkovic; Vanja Bosic; Vesna Vasic; Branislav Sakic; Sanja Bjelan; Minja Abazovic; et al. (PLoS ONE, 2025)
Background The COVID-19 pandemics caused both physical and mental health problems raising global social tension, anxiety and discomfort which toghether lead to the increase in the consumption of psychoactive substances, among which alcohol was the most common, as a way of self-help. The hypothesis of this paper is the rising number of type II (anxious model) and type III (depressive model) alcohol dependent patients (as identified by the Lesch Typology) in the post-COVID-19 pandemic period compared to the pre-pandemic period, as a likely consequence of the stress, fear, problems and adversities that were caused by the pandemic. Method The research was conducted as a retrospective cross-sectional study. It included 218 patients who were diagnosed with alcohol dependence. To classify the patients by the Lesch Typology, the MS Windows softer package for data processing available in public domain was used. Results In relation to the Lesch Typology, 111 (50.9%) patients belonged to type III, 45 (20.6%) to type I, 37 (17.0%) to type II and 25 (11.5%) to type IV. Conclusion Compared to the pre-pandemic findings of alcohol dependents classification according to the Lesch Typology, there was no increase in types II and III after the COVID-19 pandemic.